2007
DOI: 10.1152/ajpendo.00364.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose-dependent insulinotropic peptide on osteoclast function

Abstract: -Acute nutrient ingestion leads to a rapid inhibition of bone resorption while effects on makers of bone formation are less marked or absent, suggesting that there is a transient shift toward skeletal accretion in the immediate postprandial period. The cellular bases for these effects are not clear. Glucose-dependent insulinotropic peptide (GIP), a known modulator of glucose-induced insulin secretion, is secreted from intestinal endocrine cells in response to nutrient ingestion. In addition to the effect of GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 29 publications
2
113
0
5
Order By: Relevance
“…(3) GIP stimulates collagen type I synthesis and increases alkaline phosphatase activity in osteoblasts consistent with an anabolic effect on these cells. (2) In addition, GIP inhibits osteoclastic differentiation and activity.…”
Section: G Lucose-dependent Insulinotropic Peptide (Gip) Ismentioning
confidence: 76%
See 1 more Smart Citation
“…(3) GIP stimulates collagen type I synthesis and increases alkaline phosphatase activity in osteoblasts consistent with an anabolic effect on these cells. (2) In addition, GIP inhibits osteoclastic differentiation and activity.…”
Section: G Lucose-dependent Insulinotropic Peptide (Gip) Ismentioning
confidence: 76%
“…(2) In addition, GIP inhibits osteoclastic differentiation and activity. (3) The net effect in vivo is that elevations of GIP result in an increase in bone mass, (4) whereas the absence of GIP signaling results in significantly lower bone mass. (5,6) We have previously reported on the development and characterization of GIP-overexpressing transgenic (Tg + ) mice.…”
Section: G Lucose-dependent Insulinotropic Peptide (Gip) Ismentioning
confidence: 99%
“…There are GIP-specific receptors located on osteoblasts (25) and osteoclasts (26). GIP operates as an anabolic hormone in the bone, where it stimulates incorporation of meal-derived Ca 2+ into bone and bone building (13), and reduces bone absorption by inhibiting osteoclastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…93 Further, GIP inhibits osteoclast differentiation, resulting in decreased resorption. 94 Fasting and postprandial GIP levels were found to be reduced after RYGB. 95 In one study GIP levels were found to be reduced after RYGB but only in diabetic patients.…”
Section: Impact Of Bariatric Surgery On Bone Metabolismmentioning
confidence: 92%